Teenage Fertility and High School Completion - Ribar, David C. (The Review of Economics and Statistics, 1994)
This paper uses 1979-85 data on women from the National Longitudinal Survey of Youth to examine the eco-nomic, sociological, and institutional antecedents of adolescent childbearing and high school completion and to analyze the effect of early childbearing on school completion. Fertility and school completion are modeled as dichotomous outcomes, and their determinants are estimated using a bivariate probit specification. The paper finds evidence that adolescent childbearing is an endogenous determinant of high school completion and that failing to account for this endogeneity leads to an over-estimate of the schooling consequences of early childbearing.